THE CHARACTERISTICS OF SPORT RECREATIONAL PARK USE IN SZEGED’S ERZSÉBET LIGET - Tóth, Larissza; Győri, Ferenc (Stadium - Hungarian Journal of Sport Sciences, 2023)
Objective: Our research was aimed to explore the opportunities Szeged’s largest park, the Erzsébet Liget’s offers in the area of sport recreation, in addition, the composition, the sports habits, and the contentment of the park’s adult visitors who came from nearby and also from more distant places. We hypothesized that the characteristics of access to the park and the characteristics of park use depend on the proximity of the user’s residence. At the same time, their socio-demographic features and contentment are unrelated. Method: Our primary data were gained using random paper-based questionnaires (N=108). Those people were asked who was doing some physical exercise at various sports scenes in the park. Pearson’s Chi-square test was used to explore the relationship between different categorical variables. Results: The proximity of the park and the users’ place of residence was strongly related to the travel time and the chosen mode of transport. At the same time, it did not show any significant relation to the features of park use for sports. These features, primarily due to the elderly visitors, only impacted the frequency of park visits with an aim other than sport. Also, no significant difference was found concerning the park’s proximity, contentment with the services, and socio-demographic variables, although some tendencies were identified. Conclusion: The park’s proximity did not have an impact of significance concerning the composition and the contentment of park visitors and their use of the sports facilities.